2018
DOI: 10.26456/vtbio20
|View full text |Cite
|
Sign up to set email alerts
|

Main Trends of Biodiversity Dynamics After Natural and Anthropogenic "Catastrophes" in Spruce Forests of the European Part of Russia

Abstract: We analyzed the main trends of the change in the species richness of phytocenoses after catastrophic natural (beetle outbreaks, windfalls) and anthropogenic (clear cutting) disturbances. We examined the dynamics of the structural diversity of species richness of herb-dwarf scrubs layer with different reforestation technologies after the death of spruce stands. The study of similarity and ordination of vegetation showed the proximity of the undamaged forest to the unharvested stand, and the difference of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In the case of catastrophic windfalls, the scale of the loss of the stand and the ground cover varies, and the soil cover damage is minor [3]. With partial preservation of the forest stand and undergrowth in windfalls, only a redistribution of dominant species with a slight change in the species composition occurs in the herb-dwarf shrubs layer [2,4]. In areas of spruce drying during outbreaks of the eight-dentated bark beetle, the soil and ground cover remains mostly untouched, but the proportion of dead spruce varies from 0 to 100 %.…”
Section: The Intensity Of Disturbances In Phytocenoses After Natural mentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of catastrophic windfalls, the scale of the loss of the stand and the ground cover varies, and the soil cover damage is minor [3]. With partial preservation of the forest stand and undergrowth in windfalls, only a redistribution of dominant species with a slight change in the species composition occurs in the herb-dwarf shrubs layer [2,4]. In areas of spruce drying during outbreaks of the eight-dentated bark beetle, the soil and ground cover remains mostly untouched, but the proportion of dead spruce varies from 0 to 100 %.…”
Section: The Intensity Of Disturbances In Phytocenoses After Natural mentioning
confidence: 99%
“…With the complete destruction of spruce forest stand (not only the dead trees) in the course of clear cutting, a radical change in the soil cover [6] and transformation of forest communities into grass and shrub communities occurs, which leads to a fundamental change in the vegetation cover. In newly formed meadow communities, biodiversity increases dramatically due to emergence of non-forest species [2]. Additionally, a metaanalysis of the results of 238 studies of biodiversity in various forests of the world revealed an increase in the species richness of vascular plants after catastrophic windfalls and death of the forest stand as a result of outbreaks of bark beetles and logging [7].…”
Section: Increase Of Biodiversity: Species Richness and Structural DImentioning
confidence: 99%
See 2 more Smart Citations
“…These conventional ideas are based on the comparison of data from different researchers, construction of spatiotemporal patterns, etc. However, identification of change patterns in species composition of communities can only be done by monitoring of the biodiversity of permanent sample plots in a series of plant communities along a relief gradient within a limited area (phytocatenae) for a long period of times after catastrophic disturbances [2].…”
Section: Introductionmentioning
confidence: 99%